Implementasi Social Entrepreneurship pada Koperasi Wanita Srikandi - Hartanti, Vegy Dwi; Setiaji, Khasan (Universitas Pendidikan Ganesha, 2020)
The study aims to knownÂ what motivation which underlie the business founder to chooseÂ social entrepreneurship in establishing Koperasi Wanita (Kopwan) Srikandi, how the implementation of social entrepreneurship implemented on the activities of Kopwan Srikandi, and the impact appeared of the implementation social entrepreneurship in Kopwan Srikandi. The study was used qualitative approach with case study design. The techniques of collecting data used in this study are observations, interviews, and document studies. Data analysis techniques used in this study was by collecting data, data reduction, presentation and conclusion. The result of this research show that in the establishment of Kopwan Srikandi, it underlie by the consciousness of the founder in seeing and identifying the social problems in society, then implemented in a business entity that is a cooperative with a social mission which is expected to solve the problems. Kopwan Srikandi have two business units, there are saving and loan unit and production unit in which both of them implement the social entrepreneurship. It can be seen from the existence of cooperative entrepreneurs and type of activities that contain a social values. The impacts of social entrepreneurship appeared in Kopwan Srikandi are the improvement of human resources, the development of local natural resources and the improvement of the economic activities of the community.